Ectopic Pinealolvia in Infundibular Region. Clinical and Histopathologic Study - Altamirano, Alfredo E. (1963)
Neoplasms of the pineal gland are relatively rare, corresponding to 0.4 to 1% of all intracranial tumors, according to the series published by Zülch (24) in 1956. The term pinealoma attributed to Krabbe with which a tumor of the pineal parenchymal cells are meant for those used interchangeably neoplasia s formed at the expense of mature or immature cells.